Music in Sporting Practices: A Study on Traditional Archery Team - Yılmaz Ünlü; Adem Solakumur; Murat Kul; Miraç Makul (Journal of Educational Issues, 2024)
Sport is an important phenomenon that supports psycho-social and physical development in both individual and social contexts. Music has an important place among the factors affecting the sportive process. In this study, the effect of music on sportive activities was examined according to some demographic factors in the context of motivation, physical strength and performance, and psychological resilience. The research data were obtained from 36 athletes competing in the archery branch in the 2020-2021 season Senior Turkey Championship Final Competitions. Scanning model was used in the research. In this context, the Effect of Music on Sportive Practices scale developed by Karayol and Turhan (2020) was used. In the analysis of the data, descriptive statistics for demographic variables, the Mann-Whitney U Test, which is a nonparametric test, to test the difference between the mean of two independent groups, and the Kruskal Wallis Test, which is one of the nonparametric tests, were used to compare more than two independent groups. In addition, Spearman test was applied to determine the relationship between two or more variables. As a result of the research, there were no significant differences according to the variables of gender and personal income, but significant differences were found between the variables of education status, listening to music in training and training place and some sub-dimensions of the scale. According to this; Significant differences were found in favor of those with university education, those who listen to music in training and those whose training place is in the district. In addition, a negative significant relationship was found between listening to music in sports activities and daily training time. According to the findings, the effect of music in sportive activities decreases as the training time increases, and listening to music during training increases motivation and performance.